Arm Rehabilitation Monitoring System using LabVIEW - Mohd Zain, Muhammad Fathi; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2021)
Paralysis typically involves injury to the central nerve, especially the brain stem. In physical therapy, the development of an arm rehabilitation monitoring system with LabVIEW focuses on mobility, which helps to maintain and strengthen the resilience of a wounded organ. The unique feature of this arm rehabilitation monitoring system is the patient and practitioner can observe the patient’s progress. LabVIEW can display data of how much the patient is able to hold and lift the arm. An electromyogram sensor to measure muscle contraction and force sensitive resistance to the hand was used in this project. Then, the LabVIEW software was utilized as an interface of the system and to display the output. The project was tested on two males and two females with different body mass indices (BMI). The results concluded that the grip strength for males and females is different. Factors that affect the results are age, gender, nutrition, and BMI. The experimental results show that a person with a normal BMI puts high pressure on the grip, where the grip strength indicates a measure of muscle strength. In conclusion, the development of an arm rehabilitation monitoring system is crucial since it shows the patient’s healing progress and allows the expert to understand how long does it take for the patient to recover fully.